Recruitment and retention strategies and the examination of attrition bias in a randomised controlled trial in children’s centres serving families in disadvantaged areas of England - Hindmarch, Paul; Hawkins, Adrian; McColl, Elaine; Hayes, Mike; Majsak-Newman, Gosia; Ablewhite, Joanne; Deave, Toity; Kendrick, Denise (BioMed Central, 2015)
Background